بناء برنامج معجمي للألفاظ المهملة في مقامات السيوطي : دراسة تحليلية - Nurul Atikah Rahman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to detect the neglected and difficult words in Maqaama Al-Suyuti made by the students specializing in the Arabic language studies at the International Islamic University Malaysia, IIUM while reading these Maqa>ma. The researcher focuses on the neglected and difficult words. These words were analysed by using the latest speech processing computer programs like Intellyze 3. The research participants were chosen among experts at the Department of Arabic Language and Literature from Kulliyyah Islamic Revealed Knowledge and Human Sciences at the International Islamic University Malaysia, Gombak, Malaysia. Then, the researcher chose three experts, all from Arabic countries. They were selected based on their experience in the field of language and literature. For the purpose of gathering information, this study used the computer software Intellyze 3, HTML software and audio recording. The researcher chose three of Maqaama Al-Suyuti which are Maqama At-Tufahiyyah, Maqama Al-Miskiyyah and Maqama Al-Yaqutiyyah as the subject of this study. The results of this study demonstrate the neglected and difficult words in Maqama Al-Suyuti, the most difficult Maqama being Maqama At-Tufahiyyah which reached the percentage of 67% of non-Arabic words. In light of the findings of the results, the researcher suggests a number of recommendations and proposals at the conclusion of the research.